Improving Reading Skills of Seventh Grade Students of SMP N 5 Padang by using Picture Story Book in The Academic Year of 2019/2020 - Herlini Deyandra (Lesson Journal: Languange, Applied Linguistics, and Education Journal, 2020)
This action research aimed to improve reading skills of the seventh grade of SMPN 5 PADANG by using Story Book. Reading could give the best solution for teacher to improve all of the student’s skill in English. The data will obtain from the observation during the implementation of reading the Story Book, giving a task. This Research will use Car (classroom Action Research) method. The data was qualitative in research. Researcher used Pre-test and Post Test and Interview to collect the result and find. The subject of this research is students of VII 1 Grade of SMP N 5 Padang in Semester 1. This research showed the achievement from Pre-test and Post-test. The score Pre-test (71,40) and Post-test (73,28) as the result from the research. Based on the result and finding it can conclude that Picture Story Book can improve reading skill. This test used narrative text method to make the question test. Picture story book could recommend as a media to teach reading activity. Also based on the interview students showed their interesting in reading activity used picture story book.